A Miss-step of Innovation and Marketing Strategies Plan: Can OPPO Find a Way Out? - Zhen Yang Jin; Mariam Ben Saif; Daisy Mui Hung Kee; Ghezlan Al Basis; Majdi Anwar Quttainah; Annis Afifah; Sarah Rifhani; Qishen Huang (AIBPM Publisher, 2020)
OPPO as a young Chinese mobile phone brand, it has to tackle many difficulties to survive in the competitive Red Sea of mobile industry, such as: lack of innovation of technology and core chips, short of complete product supply chain. All these factors may restrict and limit the further development of OPPO. The purpose of this paper is to examine and analyse how could OPPO find a way out of the competitive mobile industry. By researching the previous data, questionnaire for the public, and analysing the previous strategies of OPPO. Eventually we will provide some suggestions and idea for OPPO to tackle those problems and would benefit OPPO in the long-term.